230k views
5 votes
What is the solution to this system of linear equations 7x-2y=-6
8x+y=3

User MmixLinus
by
5.8k points

2 Answers

3 votes

Answer: B

Explanation:

User Yaniv Aknin
by
3.9k points
4 votes

Answer:

(0,3)

Explanation:

7x-2y=-6

8x+y=3

Multiply the second equation by 2 so we can eliminate y

2(8x+2y) = 2*3

16x+2y=6

Add the first equation to the modified second equation

7x-2y=-6

16x+2y=6

--------------------

23x = 0

Divide by 23

23x/23 = 0/23

x =0

Now we need to find y

8x+y = 3

0+y =3

y=3

(0,3)

User JuanFernandoz
by
4.4k points